2017
DOI: 10.1111/gbb.12394
|View full text |Cite
|
Sign up to set email alerts
|

A single bout of exercise increases hippocampalBdnf: influence of chronic exercise and noradrenaline

Abstract: Research in human subjects suggests that acute exercise can improve memory performance, but the qualities of the exercise necessary to promote improved memory, and the signaling pathways that mediate these effects are unknown. Brain-derived neurotrophic factor (Bdnf), noradrenergic signaling, and post-translational modifications to AMPA receptors have all been implicated in the enhancement of memory following emotional or physical arousal; however, it is not known if a single bout of exercise is sufficient to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 85 publications
(209 reference statements)
2
26
2
Order By: Relevance
“…We have previously shown that continuous exposure to a voluntary running wheel for one month resulted in an increase in the expression of GluR1 and phosphorylation of Ser845 . However, we observed no change in Ser845 phosphorylation 15 minutes after a single 45‐minute bout of treadmill exercise . Hu et al found elevated Ser845 phosphorylation 15 minutes following a peripheral injection of epinephrine, suggesting that the phosphorylation of Ser845 is induced rapidly.…”
Section: Introductioncontrasting
confidence: 65%
See 2 more Smart Citations
“…We have previously shown that continuous exposure to a voluntary running wheel for one month resulted in an increase in the expression of GluR1 and phosphorylation of Ser845 . However, we observed no change in Ser845 phosphorylation 15 minutes after a single 45‐minute bout of treadmill exercise . Hu et al found elevated Ser845 phosphorylation 15 minutes following a peripheral injection of epinephrine, suggesting that the phosphorylation of Ser845 is induced rapidly.…”
Section: Introductioncontrasting
confidence: 65%
“…Similarly, stimulation that reduces synaptic strength is associated with a rapid dephosphorylation of Ser845 . We have previously shown that continuous exposure to a voluntary running wheel for one month resulted in an increase in the expression of GluR1 and phosphorylation of Ser845 . However, we observed no change in Ser845 phosphorylation 15 minutes after a single 45‐minute bout of treadmill exercise .…”
Section: Introductioncontrasting
confidence: 62%
See 1 more Smart Citation
“…4 Lower serum levels are linked to greater symptom, cognitive, impairment. 5 Thus, interventions, as for example physical exercise, whether acute or chronic, endurance or resistance, promote the mobilization of BDNF and other neurotrophic factors 6,7 In the laboratory environment, several experimental models have been shown to accelerate the ageing process through disruptions in the normal functioning and integrity of BDNF. Social isolation/ deprivation of rats and mice induces chronic stress and may be applied usefully as a laboratory animal model for neuropsychiatric disorders, such as schizophrenia spectrum disorders and clinical depression.…”
Section: Editorialmentioning
confidence: 99%
“…Importantly, BDNF is a candidate mechanism underlying these exercise-induced benefits that help optimize brain plasticity outcomes via exercise intervention (Baptista and Andrade, 2018;Cooper et al, 2018). Acute high-intensity exercise increases the expression of BDNF (Venezia et al, 2017). Furthermore, MicroRNAs (miRNAs), small non-coding regulatory RNAs, are important regulators of various cellular processes via several signaling pathways relevant to exercise adaptation (Domańska-Senderowska et al, 2019).…”
Section: Introductionmentioning
confidence: 99%